Analisa Perencanaan Persediaan Guna Mengatasi Kelebihan Stok Beras pada UD Berkah Niaga Pangan - Adonis Kurniawan; Puspanantasari Putri, Erni (Fakultas Teknik UMRI, 2024)
Inventory planning is an important process in the company's operational process. The main objective of inventory planning is to ensure that the company has optimal and efficient raw material inventory, thereby minimizing inventory costs and storage costs for the company. UD Berkah Niaga Pangan is a company focused on being a rice distributor to meet local market needs. For data processing, the company uses the Economic Order Quantity (EOQ) method to effectively plan raw material requirements. Calculations are performed using forecasting methods such as Moving Average, Single Exponential Smoothing, and Naïve, resulting in an annual Total Inventory Cost of Rp. 64,555,000.